Practical application of a nutraceutical in age-related macular degeneration - T.G. Kamenskikh; Kolbenev I.O; Veselova E.V; Batischeva Yu.S. (РМЖ "Клиническая офтальмология")
Kamenskykh T.G., Kolbenev I.O., Veselova E.V., Batischeva Yu.S. Saratov State Medical University named after V.I. Razumovsky Age-related macular degeneration (AMD) occupies one of the leading places among diseases leading to visual impairment and blindness. Aim: to evaluate the results of the use of Retinorm in patients with a «dry» form of AMD based on optical coherence tomography (OCT) and multifocal electroretinography (MF-ERG) data. Patients and Methods: 40 patients (66 eyes) with a «dry» form of AMD (drusen) participated in the study. Group 1 — 20 patients (34 eyes) who received Retinorm 1 capsule 3 per day during meals, group 2 — 20 patients (32 eyes) who received standard conservative therapy for 16 weeks. The standard examination included static perimetry, OCT, OCT-angiography, MF-ERG. Results and Discussion: A statistically significant change in the total perfusion density in the foveal area was observed in patients with small hard drusen in the Retinorm group. The thickness of the retina in patients of group 1 was 258±31 μm before treatment and did not change significantly during the treatment. In group 2, the thickness of the retina in the foveal region was 245±46 μm before the study and 312±28 μm in 6 months. Normalization of the configuration of a three-dimensional image of MF-ERG was observed in 75% of patients in group 1, while in group 2, the electrophysiological parmeters worsened in 60% of patients. Within 6 months, no significant change in visual acuity was detected in both groups, but in group 2 there was a tendency to its decrease. The improvement of well-being and a decrease of complaints was noted in group 1, and in group 2 there were no changes. Conclusions: Retinorm, as a balanced source of substances necessary for the retina, can be recommended for the use in the complex therapy of patients with a «dry» form of AMD. Key words: age-related macular degeneration, drusen, optical coherence tomography, angiography, Retinorm. For citation: Kamenskykh T.G., Kolbenev I.O., Veselova E.V., Batischeva Yu.S. Practical application of a nutraceutical in age-related macular degeneration. RMJ “Clinical ophthalmology”. 2018;2: 107–112.